2012
DOI: 10.1182/blood-2011-09-371153
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of published single nucleotide polymorphisms associated with acute GVHD

Abstract: Candidate genetic associations with acute GVHD (aGVHD) were evaluated with the use of genotyped and imputed singlenucleotide polymorphism data from genome-wide scans of 1298 allogeneic hematopoietic cell transplantation (HCT) donors and recipients. Of 40 previously reported candidate SNPs, 6 were successfully genotyped, and 10 were imputed and passed criteria for analysis. Patient and donor genotypes were assessed for association with grades IIb-IV and III-IV aGVHD, stratified by donor type, in univariate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
2
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 51 publications
3
85
2
2
Order By: Relevance
“…3 In this cohort study, Cox regression models were used to examine allelic (additive) and genotypic (dominant and recessive) associations of donor and recipient SNPs with the risk of sclerotic GVHD. 10 Results were analyzed without and with adjustments for clinical risk factors as defined in our previous study. 3 These included stem cell graft source, HLA matching at A, B, C, DRB1, and DQB1 loci, donor-recipient ABO compatibility, and total body irradiation (TBI) exposure.…”
Section: Discussionmentioning
confidence: 99%
“…3 In this cohort study, Cox regression models were used to examine allelic (additive) and genotypic (dominant and recessive) associations of donor and recipient SNPs with the risk of sclerotic GVHD. 10 Results were analyzed without and with adjustments for clinical risk factors as defined in our previous study. 3 These included stem cell graft source, HLA matching at A, B, C, DRB1, and DQB1 loci, donor-recipient ABO compatibility, and total body irradiation (TBI) exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Of all methotrexate's candidate genes previously examined, MTHFR, in particular the non-synonymous C677T (rs1801133) and the A1298C (rs1801131) polymorphisms, has received great attention but yielded conflicting results. 18,23,24,[29][30][31]46 In this study, associations were found between MTHFR genetic status and grade II-IV acute GvHD; none, however, remained positive for severe acute GvHD after correction for multiple testing. Based on our data, it is suggested that the SNP associated with grade II-IV acute GvHD herein are either: (i) associated with a less severe form of the disease (grade II), and/or (ii) the lower MAF (<20%) of these variants did not allow us to demonstrate their associations with grade III-IV acute GvHD occurring at a frequency of 15% in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The sequencing of the entire genome of an organism, or whole genome sequencing (WGS), has been used to generate de novo genome assemblies of cancerous cell genomes, 4 numerous model organisms, 5 the human gut microbiome 6 and to identify rare disease-causing mutations. 7 WGS, while comprehensive and necessary when there is no established reference sequence of an organism, is still relatively expensive. Moreover, since the biological function of the much of the non-protein encoding human genome has yet to be elucidated, functional annotation of many new (and existing) variants is difficult to interpret.…”
Section: Box 1 New Genomics Technology In Hctmentioning
confidence: 99%
“…7,26,31 Such a model will need to differentially weigh HLA and non-HLA factors based on their ability to predict the likelihood and severity of TRM and GVHD. As allele-level HLA typing and non-HLA genetic data are now cataloged for patients across large allogeneic HCT recipient databases, multi-variate risk prediction algorithms developed using complex and large-scale genomic data may enable the development of risk-prediction algorithms.…”
Section: Application Of Sgs Technology To Gvhd Risk Assessment Beyondmentioning
confidence: 99%
See 1 more Smart Citation